Language: An Archive of History and Experience in Kamila Shamsie’s Novels - Naila Sahar (Journal of Research in Humanities, 2019)
Kamila Shamsie is a Pakistani novelist who represents the new generation of writers writing in English. In her novels, she makes language a means and tool to consolidate the identity of her nation through her syncretic linguistic strategy of appropriation and abrogation of English. She combines her poetic English prose with Urdu words and phrases and gives her readers a glimpse of her native culture and tradition. This paper will discuss certain techniques which allow Shamsie to bring to consciousness and articulation a richly tessellated society which is subsisting under the weight of destructive cultural encounter, i.e. the encounter between East and West. Shamsie’s alchemic response to the crisis and confusion in the country is impressive exploration of linguistic permutation in her narration. She resolves the pull between native and imported or received language by hybridizing her discourse through metonymic gap, syntactical and lexical abrogation, appropriation and syntactic relexification. The paper will elaborate as to how Shamsie seizes and replaces the borrowed English language to adapt it to her own usage and negotiates the gap that exist in different nations in the world at large.